PENGARUH PENDIDIKAN KESEHATAN DENGAN METODE SIMULASI TERHADAP PRAKTIK CUCI TANGAN PAKAI SABUN PADA ANAK SEKOLAH DASAR NEGERI CIBEUREUM KOTA TASIKMALAYA - Nur Rosdiyawati; Iseu Siti Aisyah; Siti Novianti (Jurnal Kesehatan Komunitas Indonesia, 2023)
Diarrhea is a disease where the condition of defecation with a liquid or soft consistency and the frequency is more than three times a day. Cibeureum sub-district was ranked first in cases of diarrhea aged 5-14 years, as many as 311 cases out of a total of 23,370 cases (2019-2020). In 2020-2021 (January to November) there were 248 cases of diarrhea with a percentage of 61.2% of patients at the elementary school (SD) level. SDN Cibeureum was ranked first with the number of diarrhea cases as many as 25 cases. Hand washing behavior that does not meet health requirements is at risk of developing diarrhea. Children tend to have a habit of not keeping their hands clean by washing their hands, especially at school. Efforts to improve the practice of washing hands with soap (CTPS) can be done through health education using interesting methods. Simulation is a learning method that is considered suitable for community skills. The research design is a pre-experimental design research with a one group pretest-posttest research design. The research subjects were 57 grade 1 students at Cibeureum State Elementary School, Tasikmalaya City. Data collection tools using observation sheets. The results of statistical tests with the Wilcoxon test, namely (1) obtained p-value = 0.001 concluded that there is an effect of health education with the simulation method on CTPS practice immediately after being given treatment and (2) obtained p-value = 0.001 concluded that there is an effect of health education with the method simulation of the practice of CTPS one week after being given treatment. Schools are advised to provide adequate facilities to implement CTPS, provide information about CTPS regularly to students and conduct learning using the simulation method.